Effects of Mn‐doping on the Structural and Electrochemical Properties of Na3Ni2SbO6 for Sodium‐Ion Battery. Issue 5 (30th April 2020) - Kee, Yongho; Put, Brecht; Dimov, Nikolay; Staykov, Aleksandar; Okada, Shigeto
Abstract: Invited for this month's cover picture is the group of Prof. Shigeto Okada. The cover picture shows 2 kinds of synthesized Mn‐doped Na3 Ni2− x Mn x SbO6 layered oxide cathode materials for Na‐ion batteries. The heavily doped ( x =0.5) sample in the right side suffers from large polarization, corresponding to the reduced two‐phase reaction range and a large volume change of the unit cell upon sodium extraction. On the other hand, the lightly Mn‐doped ( x =0.25) sample in the left side shows enhanced O'3–P'3 phase transition kinetics due to the smaller volume change of the unit cell. Read the full text of the Article at 10.1002/batt.201900166 . Abstract : "To us, it was quite natural to ask the question whether Ni could be partially replaced by other transition or non‐transition metals…." Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article on 10.1002/batt.201900166 .